Bagaimana Pengaruh Kenaikan PPN 12 % di Indonesia - Arba, Ivan; Arizah, Ainun (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Value Added Tax (VAT) is a type of indirect tax imposed on the consumption of goods and services in the country. This study aims to find out how the increase in VAT to 12% affects Indonesia. The results of this study show that the policy of increasing VAT has elicited a public response dominated by rejection, mainly due to concerns over the increasing economic burden on low-income people. A number of studies have also identified potential negative macroeconomic impacts, such as rising inflation, weakening purchasing power, and an increase in the number of people at risk of poverty. The MSME sector is also affected by low tax literacy, limited capital, and the readiness of their administrative system to adjust policy changes. Although there is an opportunity to strengthen the digitalization of the tax system to improve compliance, this policy is considered to need to be balanced with a more inclusive and equitable strategy. An approach that takes into account the socio-economic conditions of the community and is in line with the values of Pancasila is important so that the increase in VAT does not deepen social inequality and still supports sustainable economic growth.